NeuroProtect, a Candidate Formula From Traditional Chinese Medicine, Attenuates Amyloid-β and Restores Synaptic Structures in APP/PS1 Transgenic Mice - Tan, Yan; Wang, Xu; Zhang, Jiani; Zhang, Huawei; Li, Haiyan; Peng, Tiantian; Chen, Weihang; Wei, Peng; Liu, Zhaoheng; He, Fang; Li, Jiao; Ding, Haimin; et al. (Frontiers in Pharmacology, 2022)
Background: Alzheimer’s disease (AD) is the most common cause of dementia. The emerging data suggest that the cognitive decline occurred in the setting of Aβ accumulation plus synaptic dysfunction, which started to happen at preclinical stages. Then, presymptomatic intervention is more critical to postponing AD processing. Traditional Chinese medicine has a long history of treating and preventing dementia. Findings have shown that the decoction of Panaxnotoginseng and Gardenia jasminoides Ellis enhances memory functions in patients with stroke, and their main components—Panax Notoginseng Saponins (PNS) and geniposide (GP) improved memory abilities in experimental AD models. Since herbal medicine advantages in protection with few side effects, we wish to extend observations of the NeuroProtect (NP) formulation for reducing amyloid-β and restoring synaptic structures in APP/PS1 transgenic mice. Methods: APP/PS1 transgenic mice and their wild-type littermates fed with control, NP, and their components from 4 to 7 months of age. We assessed the synaptic structure by Golgi Staining, analyzed the amyloid deposits by Thioflavin-S staining, measured related protein levels by Western blot or ELISA. We used the Morris water maze and shuttle box test to evaluate cognitive functions. Results: Compared to WT mice, APP/PS1 mice are characterized by the accumulation of amyloid plaques, reducing synaptic structure richness and memory deficits. NP prevents these changes and ameliorates cognitive deficits. These effects may have been due to the contribution of its components by inhibition of insoluble amyloid-β deposition and restoration of synaptic structures. Conclusion: These findings reveal a beneficial effect of NP on AD progression under an early intervention strategy and provide a food supplement for AD prevention.